Assessments of Air Pollution Control Effectiveness Based on a Sharp Regression Discontinuity Design —Evidence From China’s Environmental Big Data - Wang, Ren; Huang, Jiaqi; Zhang, Lizhi; Xia, Yu; Xu, Xu; Nong, Tongli (Frontiers in Environmental Science, 2021)
The Assessment and Appraisal Method for Ecological Construction Targets (the Method) was promulgated in 2016, which provided concrete instruction for China’s air pollution control and established an explicit standard for reducing air pollutants concentration. This study implements a sharp Regression Discontinuity (RD) design and makes an assessment on air quality control effectiveness of the Method based on the high-volume big data acquired from 173 cities in China. Results show that the Method has significantly improved air pollution control on the overall air quality index (AQI), and reducing concentrations of PM2.5, PM10, SO2, NO2, and CO across the country in the observation periods. No reduction effect was observed for O3 though. The robustness tests support the conclusion as well. Besides, the heterogeneity analysis illustrates that the policy had a significant short-term treatment effect in East, South, Central, North, Northwest, Southwest, and Northeast China. However, the Method’s effect is found to decline over time either nationwide or regionally according to the persistence analysis. Therefore, this article puts forward several suggestions regarding the formulation of long-term regulations for air pollution control, the transformation of the growth model for sustainable development, and optimization of incentives system for improved pollution control and prevention